Analisis Kinerja Ruas Jalan Akibat Hambatan Samping: Studi Kasus Pasar Tradisional di Kota Medan - Malasyi, Syibral; Mukhlis, M; Anjella, Eva; Fauzan, M; Mudi Hafli, T; Sarana, David; Fasdarsyah, F (Malikussaleh University, 2023)
Road of Kapten Muslim Medan City is quite congested. due to the road is located in the area of many shops and trades that are not efficient in conducting buying and selling transactions. Primary data such as road geometrics, traffic volume, side obstacles, and speed. Based on the results and discussion, the highest side obstacle on this section of Jalan Kapten Muslim has an event weight frequency of 1087.8. This value is included in the class of very high side obstacles. The effect of obstacles on capacity is seen from the decrease in capacity before the side obstacle of 6,600 skr / hour with a Dj value of 0.47 and with side obstacles to 6,072 skr/ hour with a Dj value of 0.51. Thus, the level of road service for both is C. Thus, there is a decrease in capacity due to side barriers that can affect the performance of the road.